Examining Nature and Forest Tourism in the Era of the Covid-19 Pandemic on Sumatra Island - Hardiansyah Tambunan; Doli Witro; Ilma Amalia; Muhamad Izazi Nurjaman; Mursal Mursal (Jurnal Pariwisata Nusantara (JUWITA), 2022)
Purpose: The aims of this study is to describe and analyze what happened to nature and forest tourism on the island of Sumatra in general during the covid-19 pandemic. Methods: This study uses a qualitative method with a literature research design. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. Results: The results show that the nature and forest tourism sectors in North Sumatra, West Sumatra and Aceh have not been able to boost tourism back to its normal level. The social distancing policy is the main cause of the sluggish tourism activity on the island of Sumatra. Contribution: This research is expected to be able to provide a solution to the sluggish tourism sector during the COVID-19 pandemic.